Gram Type-Specific Broad-Range PCR Amplification for Rapid Detection of 62 Pathogenic Bacteria - Klausegger, Alfred (American Society for Microbiology, 1999)
Broad-range PCR has proven to be useful for the detection of bacteria. A set of broad-range PCR primers directed against conserved regions in the 16S rRNA gene was designed to specifically amplify either gram-positive or gram-negative bacteria. The gram type-specific broad-range PCR correctly classified all 62 pathogenic species tested.